1984
DOI: 10.1136/bmj.289.6443.461
|View full text |Cite
|
Sign up to set email alerts
|

Bereavement and cancer: some data on deaths of spouses from the longitudinal study of Office of Population Censuses and Surveys.

Abstract: Registration of cancer and mortality after the death of a spouse were assessed using data from the longitudinal study of the Office of Population Censuses and Surveys (OPCS). The study population comprised 1% of the people counted in England and Wales in the 1971 census, for whom data on subsequent vital events were linked with their census records. There was little evidence of an increase in registrations of cancer after the death of a spouse and only a slight suggestion of increased mortality from cancer. Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
1
2

Year Published

1987
1987
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(36 citation statements)
references
References 16 publications
3
30
1
2
Order By: Relevance
“…Information bias is also unlikely; the study groups were established and parenthood determined before the files were searched for evidence of cancer in the parents, and the study relied on population registers that are kept for administrative purposes. Most interestingly, our finding of an absence of association between a stressful event and cancer incidence is in line with the result of other studies that relied only on information obtained from population-based registers (Jones et al, 1984;Ewertz, 1986;Kvikstad et al, 1994). In a short-term follow-up study of a 1% random sample of the 1971 census population in England and Wales, Jones et al (1984) found little evidence of an increase in the number of registrations of cancer after the death of a spouse and only a slight suggestion of increased mortality from cancer.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Information bias is also unlikely; the study groups were established and parenthood determined before the files were searched for evidence of cancer in the parents, and the study relied on population registers that are kept for administrative purposes. Most interestingly, our finding of an absence of association between a stressful event and cancer incidence is in line with the result of other studies that relied only on information obtained from population-based registers (Jones et al, 1984;Ewertz, 1986;Kvikstad et al, 1994). In a short-term follow-up study of a 1% random sample of the 1971 census population in England and Wales, Jones et al (1984) found little evidence of an increase in the number of registrations of cancer after the death of a spouse and only a slight suggestion of increased mortality from cancer.…”
Section: Discussionsupporting
confidence: 81%
“…Most interestingly, our finding of an absence of association between a stressful event and cancer incidence is in line with the result of other studies that relied only on information obtained from population-based registers (Jones et al, 1984;Ewertz, 1986;Kvikstad et al, 1994). In a short-term follow-up study of a 1% random sample of the 1971 census population in England and Wales, Jones et al (1984) found little evidence of an increase in the number of registrations of cancer after the death of a spouse and only a slight suggestion of increased mortality from cancer. Similarly, a Danish study of 1782 breast cancer cases and 1738 control subjects found no substantial difference in the distribution of marital status of spouses of cases and controls notified to the national central population register before the breast cancer diagnosis (Ewertz, 1986).…”
Section: Discussionsupporting
confidence: 81%
“…As found in previous studies, 10,14,27 we found that bereavement had no significant effect on overall cancer incidence. (One study 13 reported a moderate effect for conjugal loss in men under the age of 74, but follow-up was too brief to ascertain incidence.)…”
Section: Incidencesupporting
confidence: 73%
“…26 The research advantages of examining parental bereavement resulting from war are manifold. First, there is a smaller probability of confounding by variables related to the loss or the environment than in studies of conjugal bereavement, 13,27 cancer in one's child, 14 or divorce. 9 Second, the status of the bereaved parent never ceases.…”
Section: Introductionmentioning
confidence: 99%
“…For other causes of death, excess mortality was observed only for women during the first two months after bereavement (SMR 223). 16 The causes of death were not analyzed in enough detail to distinguish between deaths due to a common event affecting both spouses and deaths from independent causes to which bereavement may have contributed, but a substantial excess of deaths (16 actual as opposed to 7.2 expected) occurred in women whose spouses died of violent causes;'6 a similar pattern was found in men.…”
Section: Resultsmentioning
confidence: 94%